Prospects and challenges for social media data in conservation science - Di Minin, Enrico; Tenkanen, Henrikki; Toivonen, Tuuli (Frontiers in Environmental Science, 2015)
Social media data have been extensively used in numerous fields of science, but examples of their use in conservation science are still very limited. In this paper, we propose a framework on how social media data could be useful for conservation science and practice. We present the commonly used social media platforms and discuss how their content could be providing new data and information for conservation science. Based on this, we discuss how future work in conservation science and practice would benefit from social media data.